Effect of whole soy and purified isoflavone daidzein on renal function—a 6-month randomized controlled trial in equol-producing postmenopausal women with prehypertension - Liu, Zhao-min; Ho, Suzanne C.; Chen, Yu-ming; Tang, Nelson; Woo, Jean (Clinical biochemistry, 2014)
The aim of the study was to examine the long-term effect of commonly used whole soy foods (soy flour) and purified daidzein (one major isoflavone and the precursor of equol) on renal function among prehypertensive postmenopausal women who are also equol producers, a population most likely to benefit from soy intervention. This was a 6-month double-blind, randomized, placebo-controlled trial. Two hundred seventy eligible Chinese women were randomized to either one of the three treatments: 40g soy flour (whole soy group), 40g low-fat milk powder+63mg daidzein (daidzein group) or 40g low-fat milk powder (placebo group) daily each for 6months. Fasting blood and 24-h urine samples were collected at the beginning and end of trial. Serum creatinine, cystatin C, urea, angiotensin-converting enzyme, minerals and 24-h urinary creatinine and minerals were analyzed. Estimated glomerular filtration rate (eGFR) was calculated with the Cockcroft–Gault and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. Two hundred fifty-three subjects completed the study according to the protocol. Urinary isoflavones indicated good compliance of participants. No significant changes were observed in most of renal parameters, however, there was a less decrease in eGFRcockcroft in 6-month change (p=0.044) and %change (p=0.031) with whole soy intake relative to milk placebo. Subgroup analysis among women with lowered renal function suggested whole soy consumption tended to improve markers of renal function relative to control. Six-month consumption of whole soy tended to have a modest improvement of renal function in prehypertensive postmenopausal women with lowered renal function. Future trials in subjects with more declined renal function are necessary. The trial was registered in ClinicalTrials.gov with identifier of NCT01270737. (URL: http://clinicaltrials.gov/ct2/show/NCT01270737) •We examined the long-term effect of commonly used whole soy foods and purified daidzein (one major isoflavone and the precursor of equol) on renal function among prehypertensive postmenopausal women who are also equol producers.•We found a less decrease in eGFRcockcroft in 6-month change (p=0.044) and %change (p=0.031) with whole soy intake relative to milk placebo.•Six-month consumption of whole soy tended to have a modest improvement of renal function in prehypertensive postmenopausal women with lowered renal function.